Inventory of the Black Flies (Diptera: Simuliidae) of North Africa - Belqat, Boutaïna; Adler, Peter H.; Cherairia, Mouna; Boudghane-Bendiouis, Chafika Chaoui (Zootaxa, 2018)
Published records are provided for the 52 nominal species, one undescribed morphospecies, and two cytospecies of black flies known from North Africa, with relevant literature, selected synonyms, and taxonomic comments. Morocco has the greatest simuliid diversity (44 nominal species), followed by Algeria (34 species), Tunisia (18 species), Libya (5 species), and Egypt (2 species). A new site for Simulium ruficorne Macquart is recorded for simuliid-poor Egypt.